Activity Theory for Examining the Effects of the Story Continuation Writing Task on English Writing Quality - Teng, Xuan (International Journal of English Language Education, 2023)
Given the importance of the continuation task for English learning and testing in China and recent attempts to examine second or foreign language (L2) writing process in relation to social, cultural, and historical contexts, this study draws on the framework of Activity Theory (AT) to investigate the effects of story continuation writing task (SCWT) on Chinese high school students’ writing quality. Based on performance on SCWT and responses to semi-structured interviews from eighty Chinese high school students, the findings of this study demonstrate that the exploitation of AT-informed SCWT exhibited positive effects on improving English writing quality in terms of content, structure, and language use. Students utilized the mediation within and between the activity systems to facilitate their L2 written production. This study contributes to the research on the effectiveness of SCWT through the utilization of an L2 writing instructional model that was based on AT. It also throws light on the L2 writing process mediated by the continuation task and offers pedagogical implications to the English writing classroom.